COMPARISON OF TEAR FILM BREAKUP PATTERN IN ACTIVE AND INACTIVE THYROID EYE DISEASE PATIENTS: Oral Presentation - Observational Study - Resident - dr Magdalena Purnama Soeprajogo SpM (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Thyroid Eye Disease (TED) is an autoimmune inflammatory disease of the orbit that affects orbital fat, extraocular muscles, periocular tissue and lacrimal glands. TED activity can be assessed with a Clinical Activity Score (CAS) to identify active or inactive TED conditions. Dry Eye Diseases (DED) is one of the manifestations in patients with TED with a prevalence that varies from 27%-96%. The Asia Dry Eye Society (ADES) 2017 proposed a new concept for DED diagnosis and therapy, namely Tear Film Oriented Diagnosis (TFOD) and Tear Film Oriented Diagnosis Therapy (TFOT) with Tear Film Breakup Pattern (TBUP) examination. TBUP examination help in determine specific management of DED. The aim of this study is to determine the differences in TBUP in TED patients based on active and inactive. Methods : This is an analytical observational study with a cross-sectional design. The subjects were TED patients who came to the Cicendo Eye Hospital and met the inclusion criteria. The study was conducted at the National Eye Center of Cicendo Eye Hospital in April - June 2022. The data were analyzed with the Chi-Square Test. Results : This study was conducted on 23 patients or 46 eyes. This study found a statistically significant differences in TBUP features in active and inactive TED patients (p=0.0001). The most common features of TBUP was found in active TEDs was dimples (55%). Conclusion : There are differences of TBUP features in active and inactive TED patient.